RF Power Commissioning and an Electron Beam Diagnostic Station for a New RF-gun at Chiang Mai University - N. Chaisueb (2018)
© 2016 The Authors. This paper presents results of the RF power commissioning for a new thermionic RF electron gun of the linear accelerator system at the Plasma and Beam Physics Research Facility, Chiang Mai University. The research focuses on generation and measurements of a radio-frequency wave for using as a power source for electron acceleration. The low-level RF power measurements were conducted to study the performance of the system. Then, the commissioning of the RF-gun with the high-level RF power obtained from a new 7-MW klystron tube was performed to study the proper condition for the RF-gun operation. The gun temperature was optimized and the proper temperature was about 33oC-34oC. In nominal operation, the RF system produces the RF pulses with the repetition rate of 10 Hz for the proper RF pulse length of 3-4 μs and the maximum peak power of ∼3.9 MW. The absorbed RF peak power is 2.7 MW, which leads to the average power of 81 W. In order to investigate the influence of the asymmetric electromagnetic field distribution inside the RF-gun, an integrated electron beam diagnostic station has been developed and is installed in the accelerator beam transport line. The results of the RF commissioning and development of the diagnostic system for measurements of the electron pulse current, the transverse beam emittance and the beam energy are reported and discussed.